The effects of Anodonta cygnea biological fluids on biomineralization of chitosan membranes - Lopes, Anabela (2010)
The use of chitosan membranes, a low-cost, biocompatible material with promising capabilities in biomedical applications has already been fairly investigated in other fields with good results. Here, the aim was the in vitro mineralization assays accomplished with the chitosan membranes incubated in the control calcium and phosphate solutions on “Ussing” chambers. Biological fluids from Anodonta cygnea were added to the control solutions under different physical–chemical parameters such as pH, synthetic and natural organic compounds. Some organic compounds analyses in the solutions as well as the chitosan membrane SEM-EDS, XRD and FTIR observations were carried out at the end of experimental period. From the experiments it was shown that the chitosan membrane may act as a selective epithelium with preferred ionic movements. Particular mineral deposits, in the chitosan membrane, with hexagonal hydroxiapatite crystals, occurred only at pH 6 with HCL or succinic acid. Biological fluids of A. cygnea induced an increase in number and size of hexagonal crystals forming specific rosaceous structures, especially at pH 6 with succinic acid. It seems that proteins, GAGs and lipids can be involved on this process, since there is a significant reduction on its contents after experiments. So, further applied research with these materials can be a promising subject.